LDLCHOLESTEROLEXAMINATION (LDL-C) USINGHOMOGENEOUS ASSAY - Made DwiAmbara Putra (Universitas Udayana, 2013)
Homogeneous method describe as a method that does not require separation of free and bound label. This method has the ability tofully automate the determination of LDL-C directly small sample volume sand short examination time. In addition this method use automated pipette and control of time and temperature more accurate. There are 5 methods i.e. Solubilization homogeneous LDL-C assay (SOL) from KyowaMedex, Surfactant LDL-C assay (SUR) from Daiichi Pure Chemicals, Protecting LDL-assay reagent (PRO) from Wako Chemicals, LDL-C assaycatalase (CAT) Denka Seiken and Calixarene of LDL-C assay (CAL) from International Reagents Corporation. All method is to use a variety of detergents and other chemicals that cause blocking or dissolution of specific lipoprotein classes to achieve specificity for LDL.